2022
DOI: 10.1111/jcpe.13697
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor‐1, ‐2, and ‐6 genotypes in relation to salivary human beta‐defensin‐1, ‐2, ‐3 and human neutrophilic peptide‐1

Abstract: Aim To examine whether functional gene polymorphisms of toll‐like receptor (TLR)1, TLR2, and TLR6 are related to the salivary concentrations of human beta‐defensins (hBDs)‐1, ‐2, ‐3, and human neutrophilic peptide (HNP)‐1. Materials and Methods Polymorphisms of TLR1 (rs5743618), TLR2 (rs5743708), and TLR6 (rs5743810) were genotyped by PCR‐based pyrosequencing from the salivary samples of 230 adults. Salivary hBD‐1, ‐2, ‐3, and HNP‐1 concentrations were measured using enzyme‐linked immunosorbent assay. General … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…According to the present results, salivary HNP-1 levels elevate gradually with the increased number of pocket teeth. This finding of elevated HNP-1 levels in the periodontally diseased elderly is in line with our recent study on defensin levels in an adult population with an age range of 40-60 years [21]. A further comparison of defensin levels between the latter and present studies revealed that the levels of salivary HNP-1 in the Control group elderly were lower (median 33.4 pg/mL, range 0-329 pg/mL) than those in the adult population (median 81.9 pg/mL, range 17.4-184 pg/mL).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…According to the present results, salivary HNP-1 levels elevate gradually with the increased number of pocket teeth. This finding of elevated HNP-1 levels in the periodontally diseased elderly is in line with our recent study on defensin levels in an adult population with an age range of 40-60 years [21]. A further comparison of defensin levels between the latter and present studies revealed that the levels of salivary HNP-1 in the Control group elderly were lower (median 33.4 pg/mL, range 0-329 pg/mL) than those in the adult population (median 81.9 pg/mL, range 17.4-184 pg/mL).…”
Section: Discussionsupporting
confidence: 92%
“…Based on the present study's results, hBD-2 levels are elevated in saliva where there is an increased extent of periodontitis; however, significant differences disappeared when p values were adjusted by the Bonferroni correction for multiple tests. In our recent study on salivary defensins in working-aged adults [21], the highest hBD-2 levels were measured in the localized periodontitis group (PPD ≥ 4 mm at 2-7 teeth), whereas the hBD-2 levels did not differ between the Control and the generalized periodontitis groups (no teeth vs. ≥14 teeth with PPD ≥ 4 mm). It is possible that the decreased hBD-2 levels with the expanded burden of the infection-induced inflammation are related to the enzymatic degradation of hBDs by host-derived and bacterial proteases.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Alterations in salivary neutrophil defensin levels have been associated with oral diseases such as squamous cell carcinoma, lichen planus, glossitis associated with iron deficiency, and mandibular osteomyelitis [102][103][104]. Regarding periodontitis, recent studies have found that the levels of neutrophil defensins in SWS increased progressively with rising numbers of pocketed teeth, which can be observed in both the adult population aged between 40-60 years [105] and the elderly population aged 65 years or more [106]. The consistent elevation of salivary neutrophil defensin in patients with CP suggests its potential utility as a biomarker for periodontitis diagnosis [107].…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 activation can trigger the local release of IL‐33, which then activates ST2 receptors (Huang et al, 2020). TLR2 – 196 to −174 ins/del polymorphism has been shown to upregulate TLR2 expression in gastric and colorectal tissues (de Matos Lourenço et al, 2020; Proença et al, 2015), and TLR2 gene polymorphisms have the potential to change salivary immune‐regulating proteins (Gürsoy et al, 2022). Based on these prior studies, we expected that TLR2 rs111200466 polymorphism would alter salivary IL‐33 and sST2 levels, but this hypothesis was rejected.…”
Section: Discussionmentioning
confidence: 99%